Fiscal Decentralization and Per Capita Income Convergence between Regencies/Municipalities in Java Island - Rima Melati Anggraeni; Mohamad Khusaini; Ferry Prasetyia (Journal of International Conference Proceedings, 2022)
This study aims to analyze the existence of beta absolute convergence and beta conditional convergence, the impact of fiscal decentralization in terms of income and expenditure side on per capita income and the process of accelerating the per capita income convergence using 2015-2019 panel data of 113 regencies/municipalities obtained from Central Bureau of Statistics and the Directorate General for Fiscal Balance. Using fixed effect regression models, this study confirms that there are beta absolute convergence and beta conditional convergence in Java Island during 2015-2019. Other findings are Local Own Source Revenue and Fiscal Balance Fund have a significant positive effect on per capita income growth, while Personnel Expenditure and Capital Expenditure have a significant negative effect on per capita income growth. The results also show that all indicators of fiscal decentralization play significant role in accelerating the convergence of per capita income. Based on the results of estimates, Local Government Own Source Revenue should be optimized and quality of government spending have to be improved to foster income per capita convergence between regions in Java Island.Keywords: income per capita convergence, fiscal decentralization regional inequality, absolute beta convergence, conditional beta convergence